Long-Term Therapeutic Plasma Exchange to Prevent End-Stage Kidney Disease in Adult Severe Resistant Henoch-Schonlein Purpura Nephritis - Patrick Hamilton; Olumide Ogundare; Ammar Raza; Arvind Ponnusamy; Julie Gorton; Hana Alachkar; Jamil Choudhury; Jonathan Barratt; Philip A. Kalra (Case Reports in Nephrology)
A 27-year-old man presented with a palpable purpuric skin rash and joint and abdominal pain in April 2010. He had acute kidney injury and his creatinine quickly deteriorated to 687 μmol/L, with associated nephrotic range proteinuria. Kidney biopsy showed crescentic Henoch-Schonlein nephritis. He was treated with intravenous cyclophosphamide and prednisolone despite which his renal function deteriorated; he required haemodialysis for a short duration and seven sessions of therapeutic plasma exchange (TPE). Renal function improved, but after discharge from hospital he suffered 2 further relapses, each with AKI, in 4 months. Cyclophosphamide was not effective and therefore Rituximab was introduced. He initially had a partial response but his renal function deteriorated despite continued therapy. TPE was the only treatment that prevented rapid renal functional deterioration. A novel long-term treatment strategy involving regular TPE every one to two weeks was initiated. This helped to slow his progression to end-stage kidney disease over a 3-year period and to prolong the need for renal replacement therapy over this time.